The role of micronutrients and serum metabolites in intervertebral disk degeneration: insights from a Mendelian randomization study and mediation analysis - Jiang, Nizhou; Wang, Quanxiang; Jiang, Jian; Li, Lei (Frontiers in Nutrition, 2024)
Background Intervertebral disk degeneration (IVDD) is a complex degenerative skeletal condition, potentially influenced by micronutrients and serum metabolites in its etiology. However, the exact causal relationship between these factors and IVDD remains ambiguous. Methods The research employed a Two-Sample Mendelian Randomization (2SMR) analysis to thoroughly evaluate the causal relationship between 15 micronutrients (consisting of 7 minerals and 8 vitamins) as exposure variables, 1,091 blood metabolites, and 309 metabolite ratios as intermediary factors, and IVDD as the outcome. Additionally, reverse MR analysis and mediation analysis were carried out to validate the reliability of the results and explore the underlying mechanism by which micronutrients influence the risk of IVDD by regulating metabolites. Results Among the micronutrients examined, vitamin B12 exhibited a noteworthy negative correlation with the incidence of IVDD (OR: 0.752, 95% [CI]: 0.573–0.987, p = 0.040), indicating a potential reduction in IVDD risk with increased vitamin B12 consumption. Of the 1,091 blood metabolites and 309 metabolite ratios analyzed, 52 metabolites displayed significant associations with IVDD, primarily linked to amino acid, fatty acid, nucleotide, and sphingolipid metabolic pathways. Mediation analysis identified 4-acetaminophen sulfate as a potential mediator in the protective effect of vitamin B12 against IVDD. Conclusion This study has shown that vitamin B12 may reduce the risk of IVDD and has identified 52 serum metabolites that are associated with IVDD. Furthermore, it proposes that 4-acetaminophen sulfate could serve as a potential mechanism by which vitamin B12 exerts its inhibitory effects on IVDD.